Physicians' opinions following pharmacogenetic testing for psychotropic medication. Issue 3 (30th October 2015) - Walden, Lucas M.; Brandl, Eva J.; Changasi, Amtul; Sturgess, Jessica E.; Soibel, Alexander; Notario, Janna Fe D.; Cheema, Sheraz; Braganza, Nicole; Marshe, Victoria S.; Freeman, Natalie; Tiwari, Arun K.; Kennedy, James L.; et al.
Abstract: Pharmacogenetics seeks to improve patient drug response and decrease side effects by personalizing prescriptions using genetic information. Since 2012, by one estimate, the number of patients who have had pharmacogenetic testing has doubled and this number is expected to double again by 2015. Given the increasing evidence for genetic influences on treatment response, we deemed it important to study physicians' opinions of pharmacogenetic testing. Surveys were completed by 168 Canadian physicians who had ordered at least one pharmacogenetic test (in particular for CYP2D6 or CYP2C19) for the prescription of psychiatric medication. Our results indicated that 80% of respondents believe genetic testing would become common standard in psychiatric drug treatment and 76% of respondents reported satisfactory or higher than satisfactory understanding of the pharmacogenetic report provided. Significantly more male physicians believed they had a higher understanding of the pharmacogenetic report compared to female physicians. To our knowledge, this is the only study that has assessed physicians' opinions of pharmacogenetic testing for psychotropic medication after they had received a pharmacogenetic report. Our results demonstrate a positive opinion of physicians on pharmacogenetics and indicate great potential for future clinical application. Highlights: We tested feasibility and opinions of pharmacogenetic testing in psychiatric practice. Genetic test results on CYP2D6 and CYP2C19 were provided to physicians. Results included metabolizer status (e.g., poor or ultra-rapid) and drug treatment recommendations. Physicians were asked on their attitudes on genetic testing and opinions on the report. Most physicians reported very satisfactory understanding of the pharmacogenetic report. Most also believed that genetic testing will become common standard in drug treatment.